2022
DOI: 10.1073/pnas.2200140119
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal mechanism of a BK channelopathy in absence epilepsy and dyskinesia

Abstract: Significance BK channelopathy has been increasingly implicated in diverse neurological disorders, including epilepsy and movement, cognitive, and neurodevelopmental disorders. However, precision medicine to treat BK channelopathy is lacking. We characterized a mouse model carrying a gain-of-function BK channelopathy D434G from a large family of patients with absence epilepsy and paroxysmal dyskinesia. The BK-D434G mice manifest the clinical features of absence seizures and exhibit severe locomotor de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(44 citation statements)
references
References 72 publications
4
40
0
Order By: Relevance
“…The Racine's scale evaluation was performed as described previously. 15 The parameters and corresponding scores are summarized in Table 1 . The highest score among the parameters for each rat was considered as the score of this rat.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Racine's scale evaluation was performed as described previously. 15 The parameters and corresponding scores are summarized in Table 1 . The highest score among the parameters for each rat was considered as the score of this rat.…”
Section: Methodsmentioning
confidence: 99%
“…The Racine's scale evaluation was performed as described previously 15 . The parameters and corresponding scores are summarized in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…In a GOF knock-in murine model carrying a human BK-D434G mutation, mice showed increased susceptibility to generalized seizures and motor deficits related to hyperexcitability in cortical pyramidal and cerebellar Purkinje neurons. Importantly, blocking BK channels with paxilline suppressed seizures, motor disturbances, and neuronal hyperexcitability [ 155 ]. Similarly, a D434G mutation that produces an increase in Ca 2+ sensitivity that potentiates BK channel activity [ 231 ] was described in individuals affected by epileptic seizures and/or PNKD [ 232 ].…”
Section: Bk Channel Dysfunction In Neurological Disordersmentioning
confidence: 99%
“…Interestingly, a comprehensive study by Dong et al, recently identified locomotor defects and dyskinesia-like movements in knock-in mice carrying the equivalent KCNMA1 D434G allele 19 . Notably, locomotor defects in KCNMA1 D434G mice were partially rescued by intraperitoneal injection of Paxilline, a BK channel blocker.…”
Section: Bk Channels and Neurodevelopmentmentioning
confidence: 99%
“…D434G enhances BK channel activity by increasing the Ca 2+ sensitivity of the channel [17, 18], and heterozygosity for D434G in humans results in a complex syndrome characterised by bouts of dystonic and dyskinetic movements in the limbs, mouth, and tongue [12]. Recent work in corresponding mouse models has also shown that D434G heterozygosity enhances the firing rate of murine cerebellar Purkinje neurons and dentate granule cells by accelerating the kinetics of the fAHP [19, 20].…”
Section: Introductionmentioning
confidence: 99%